Python projects for kids : unleash Python and take your small readers on an adventurous ride through the world of programming - Ingrassellino, Jessica (Community experience distilled., 2016)
Learn to start using Python for some simple programming tasks such as doing easy mathematical calculations. Use logic and control loops to build a nice interesting game. Get to grips with working with data and, once you're comfortable with that, you'll be introduced to Pygame, which will help you wrap up the book with a cool game.